2006
DOI: 10.1002/hep.21111
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic cholestasis of pregnancy as an indicator of liver and biliary diseases: A population-based study

Abstract: Intrahepatic cholestasis of pregnancy (ICP) is a liver disorder, thought to be specific for pregnancy and to spontaneously resolve after delivery. Increased rates of gallstone formation and hepatitis C have previously been associated with ICP. However, there are no longitudinal studies to determine its significance as an indicator of subsequent liver or biliary diseases. In this retrospective cohort study with cases and controls we assessed the risk of liver and biliary diseases in 21,008 women, 10,504 with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
108
1
28

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 41 publications
2
108
1
28
Order By: Relevance
“…Some studies suggest a higher prevalence in patients with hepatitis C, cholelithiasis, and nonalcoholic fatty liver disease ( 37,39,40 ). Evaluation for alternative etiologies should be pursued if cholestasis fails to resolve aft er delivery.…”
Section: Second and Third Trimestermentioning
confidence: 99%
“…Some studies suggest a higher prevalence in patients with hepatitis C, cholelithiasis, and nonalcoholic fatty liver disease ( 37,39,40 ). Evaluation for alternative etiologies should be pursued if cholestasis fails to resolve aft er delivery.…”
Section: Second and Third Trimestermentioning
confidence: 99%
“…ICP resolves with fetal delivery to recur in 45%-70% of subsequent pregnancies and occasionally with oral contraceptives. Some rare familial cases of apparent ICP have persisted postpartum, with progression to subsequent fibrosis and cirrhosis, but 15 with more than 10,000 patients showed that patients who have had ICP subsequently have more gallstones and cholecystitis, more nonalcoholic pancreatitis, more hepatitis C, and more nonalcoholic cirrhosis. Therefore, in some patients, ICP may be an indicator of more serious subsequent liver disease.…”
Section: Intrahepatic Cholestasis Of Pregnancymentioning
confidence: 99%
“…A icterícia, quando se instala, é do tipo colestático, permanecendo durante quatro ou mais semanas. Sabe-se que as hepatites cursam com grande morbidade maternofetal, determinando muitas vezes prematuridade e óbito fetal 6 .…”
unclassified